2021
DOI: 10.1038/s41524-021-00644-z
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional coherent X-ray diffraction imaging via deep convolutional neural networks

Abstract: As a critical component of coherent X-ray diffraction imaging (CDI), phase retrieval has been extensively applied in X-ray structural science to recover the 3D morphological information inside measured particles. Despite meeting all the oversampling requirements of Sayre and Shannon, current phase retrieval approaches still have trouble achieving a unique inversion of experimental data in the presence of noise. Here, we propose to overcome this limitation by incorporating a 3D Machine Learning (ML) model combi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…Besides, the authors assume the object images are magnitude-only (no phase information), which is far from real situations. As for NNPhase [24], it aims to deal with the crystal data that the application is quite specific. Besides, LenslessNet [18] is initially designed for the phase retrieval task based on Fresnel diffraction patterns with lensless imaging systems.…”
Section: Phase-only Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the authors assume the object images are magnitude-only (no phase information), which is far from real situations. As for NNPhase [24], it aims to deal with the crystal data that the application is quite specific. Besides, LenslessNet [18] is initially designed for the phase retrieval task based on Fresnel diffraction patterns with lensless imaging systems.…”
Section: Phase-only Datasetsmentioning
confidence: 99%
“…Besides, the conditional generative adversarial network (GAN), a kind of data-driven generative method based on specific conditions [21], was adopted for reconstructing the phase information from Fourier intensity measurements [22]. Wu et al also proposed a CNN to reconstruct the crystal structures with coherent X-ray diffraction patterns [23,24]. The above methods adopt supervised learning that trains the networks with the paired ground-truth data.…”
Section: Introductionmentioning
confidence: 99%
“…This can result in a total number of summation of the order of 10 9 for a pixelated imaging plane. Although this approach is not always prohibitive on modern accelerated Graphical Processing Unit (GPU) computing facilities or High Performance Computing (HPC) facilities, there are certain redundancies (outlined below) in the standard general approach that when removed, further and significantly increases the efficiency of the calculation and enable its use in more demanding applications such as training data for machine learned phase retrieval optimisation [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that a deep neural network-based method, which is a non-iterative end-to-end method, provides rapid results for phase retrieval in 2D and 3D coherent X-ray imaging [23][24][25][26]. Moreover, there have been rapid progresses for optical tomography [27,28], ghost imaging [29,30], face detection [31], growth stage detection [32], and low photon imaging [33].…”
Section: Introductionmentioning
confidence: 99%